The scientific educational and national ethnographic nature of the writer's works - Samal K. Serikova, Serikbol K. Syzdykov, Alua V .Tanzharykova, Bidana T. Kabatay,; Tleubekova, Botakoz T. (Opción, 2019)
The study aims to investigate the scientific educational and national ethnographic nature of the writer's works via comparative qualitative research methods. As a result, if we compare oral folk literature as a rich heritage with the vast sea, then one of the most extensive currents of this sea, its largest channel is epic tales. In conclusion, the works of scientific prose presented the best examples of the development of historical consciousness and Ethnography of the nation.